First-principles study on structural stabilities, mechanical properties, and biaxial strain-induced superconductivity in Janus MoWC monolayer - Sirinee Thasitha; Prutthipong Tsuppayakorn‐aek; Anan Udomkijmongkol; Satchakorn Khammuang; Thanayut Kaewmaraya; Tanveer Hussain; Thiti Bovornratanaraks; Komsilp Kotmool (Physical Chemistry Chemical Physics, 2024)
reaching 7 K. This study offers comprehensive insights into the properties of Janus MoWC monolayer under biaxial stress, positioning it as a promising candidate for 2D straintronic applications.
Keywords: MXene and MAX Phase Materials; 2D Materials and Applications; Fuel Cells and Related Materials